The effect of Chamomile Tea on Oral Mucositis among patients Undergoing Chemotherapy: Randomized Control Trail - Bassim Akreabed, Zeina; Flaih Hassan, Ahmed (Journal of Forensic Medicine and Toxicology, 2025)
Background: The side effect oral mucositis from chemotherapy harms patients who receive high-dose treatment because it affects 9 out of 10 individuals. The current oral medication palifermin needs extra funding to treat patients especially in less developed healthcare settings.Aim of study: This study aimed to test if chamomile tea can lower the harm oral mucositis causes from chemotherapy.Material and Method: Babylon oncology center in Iraq ran an official experiment with 75 patients split into two groups during medicinal studies. Card method was used to assign patients randomly into different groups. During two weeks’ participants in the chamomile group needed to apply chamomile tea rinses to their mouths three times a day but only standard medical care applied to the control group. WHO Mucositis Scale was used to measure oral mucositis severity in patients both at the start, day 7, and day 14.Results: The chamomile treatment sig nificantly reduced oral mucositis pain for patients but worsened symptoms for control patients (p < 0.001). Out of the 20 participants, 75% had no more mucositis by day 14. oral mucositis severity related closely to cancer stage, length of che motherapy treatment and patient oral hygiene practices as tested with p values under 0.05. Standard oral care protocols for chemotherapy patients should include chamomile tea integration particularly in resource-limited healthcare facilities because it effectively decreases OM severity